Legal Analysis of Insurance Defaults: A Review of Decision No. 209/Pdt.G/2024/PN Jkt.Pst Jo. Supreme Court Decision No. 3803 K/Pdt/2025 - Rusly Rusly; Appe Hutauruk; Amin Saleh (Journal Evidence Of Law, 2026)
This study addresses two problems: (1) the application of breach of contract (wanprestasi) concerning insurance claim payments, and (2) the judges’ considerations in Decision Number 209/Pdt.G/2024/PN.Jkt.Pst. Employing a normative juridical method with statutory and case approaches, the research analyzes primary legal materials (the Civil Code, the Commercial Code, Law Number 40 of 2014, OJK regulations, court decisions), secondary materials, and tertiary materials through qualitative descriptive-prescriptive techniques. The findings reveal. First, under the Civil Code, breach of contract encompasses non-performance, late performance, defective performance, and prohibited acts, while Decision 83/PUU-XXII/2024 restricts unilateral claim rejections. Second, judges across three levels ruled the defendant committed a breach of contract because the insured object was coal, making the vessel’s accident immaterial; the Loss Ratio interpretation was reasonable; the insurer was negligent during underwriting; force majeure was proven; and the rejection lacked legal basis. Ultimately, this decision strengthens consumer protection, elevates insurer standards, ensures legal certainty, and aligns with Constitutional Court’s ruling, marking a new era in Indonesian insurance law.